A new black fly species of Simulium (Nevermannia) (Diptera: Simuliidae) from Vietnam - Takaoka, Hiroyuki; Low, Van Lun; Tan, Tiong Kai; Sofian-Azirun, Mohd; Chen, Chee Dhang; Lau, Koon Weng; Pham, Xuan Da (Elsevier, 2019)
Simulium pumatense sp. nov. is described from Vietnam, and is placed in the Simulium feuerborni species-group of the subgenus Simulium (Nevermannia) Enderlein. Its morphological characteristics include the relatively smaller numbers of the following three numerical features: inner teeth of the female mandible (15–18), minute conical processes (16) on the female cibarium, and male upper-eye facets (in 15 vertical columns and 16 horizontal rows). Keys are constructed to distinguish this species from four species of the same group in Vietnam. Our molecular analysis of the DNA barcoding COI gene shows that this species is most closely related to cytoform A of the S. feuerborni complex from Thailand.